(untitled) (Comprehensive Journal of Science, 2025)
This study aims to identify the role of financial analysis in improving the quality of credit decisions in commercial banks. From this overarching objective, the subsidiary aims are: • To uncover the level of awareness among bank employees of the importance of financial analysis and its role in assessing credit quality. • To identify the tools and methods used in financial analysis that contribute to improving the quality of credit decisions. • To highlight the challenges that impede the effectiveness of financial analysis. The study adopts a descriptive-analytical approach. The study population consists of all employees involved in financial analysis and credit decisions in public commercial banks located in Sabratah city. Data were collected through a survey questionnaire designed to reflect the study variables. Key findings: 1- High level of awareness among employees of the importance of financial analysis: they demonstrated recognition of its role in improving the quality of credit decisions and reducing risks. 2- Banks rely more on traditional tools, such as financial ratios and key indicators, while the use of more advanced tools such as cash flow analysis and comparative (benchmark) analysis remains limited. 3- Moderate-level challenges impede the effectiveness of applying financial analysis, the most important of which are: lack of qualified competencies, weak accounting information systems, and workforce pressures. 4- The overall role of financial analysis in improving credit decisions was found to be high, indicating that banks possess a solid foundation on which to build to enhance the credit process> 5- The results also indicated a correlational relationship between financial analysis and credit decisions.